2022
DOI: 10.1016/s2213-2600(21)00494-x
|View full text |Cite
|
Sign up to set email alerts
|

Lenzilumab in hospitalised patients with COVID-19 pneumonia (LIVE-AIR): a phase 3, randomised, placebo-controlled trial

Abstract: Background The pathophysiology of COVID-19 includes immune-mediated hyperinflammation, which could potentially lead to respiratory failure and death. Granulocyte-macrophage colony-stimulating factor (GM-CSF) is among cytokines that contribute to the inflammatory processes. Lenzilumab, a GM-CSF neutralising monoclonal antibody, was investigated in the LIVE-AIR trial to assess its efficacy and safety in treating COVID-19 beyond available treatments. Methods In LIVE-AIR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 25 publications
(28 reference statements)
0
81
0
1
Order By: Relevance
“…In The Lancet Respiratory Medicine , Zelalem Temesgen and colleagues 6 report on a multicentre, placebo-controlled clinical trial of hospitalised patients with COVID-19, showing that lenzilumab, a neutralising monoclonal antibody against GM-CSF, is associated with improved survival without invasive mechanical ventilation at 28 days. Lenzilumab is a monoclonal antibody that directly binds GM-CSF and is being tested for conditions such as chronic myelomonocytic leukaemia and B-cell lymphoma.…”
mentioning
confidence: 99%
“…In The Lancet Respiratory Medicine , Zelalem Temesgen and colleagues 6 report on a multicentre, placebo-controlled clinical trial of hospitalised patients with COVID-19, showing that lenzilumab, a neutralising monoclonal antibody against GM-CSF, is associated with improved survival without invasive mechanical ventilation at 28 days. Lenzilumab is a monoclonal antibody that directly binds GM-CSF and is being tested for conditions such as chronic myelomonocytic leukaemia and B-cell lymphoma.…”
mentioning
confidence: 99%
“… 25 Lenzilumab, given as a three-dose course in non-ventilated hospitalised patients, showed a benefit over standard care in the primary outcome of survival without ventilation, an effect that seemed more pronounced in patients aged 85 years or younger and with CRP concentration of less than 150 mg/L. 26 Our data suggest the effect of a single dose of namilumab on CRP concentration and WHO clinical progression score is independent of age, although this requires confirmation in larger studies. Although it is not possible to directly compare these studies given the differences in sample sizes, inclusion criteria, and study designs, the overall randomised controlled trial data suggest a benefit of GM-CSF inhibition in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, eligible patients were newly hospitalized with COVID-19 pneumonia, with SpO2 ≤94% on room air and/or requiring supplemental oxygen, but not on IMV. 23 Further analyses of LIVE-AIR trial data suggested that patients aged <85 years with CRP <150 mg/L particularly benefited from . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Target Populationmentioning
confidence: 99%
“…38 LIVE-AIR (NCT04351152) was a Phase 3, prospective, randomized, multicentered, double-blind, placebo-controlled clinical trial that evaluated the efficacy and safety of lenzilumab or placebo (in addition to institutional standard of care [SOC] in both treatment groups) in hospitalized participants with COVID-19 pneumonia. 23 Patients must have been hospitalized with an oxygen saturation (SpO 2 ) ≤94% on room air or required supplemental oxygen but had not progressed to IMV. 23 Results from the LIVE-AIR trial showed that lenzilumab plus SOC significantly improved the likelihood of achieving survival without ventilation (SWOV) a (sometimes referred to as ventilator-free survival) by day 28 compared with placebo plus SOC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation